Genome Analysis of Rhodococcus Sp. DSSKP-R-001: A Highly Effective β-Estradiol-Degrading Bacterium. (28th October 2018) - Zhao, Hongyan; Tian, Kejian; Qiu, Qing; Wang, Yu; Zhang, Hongyan; Ma, Shuang; Jin, Shenbao; Huo, Hongliang
Abstract : We screened bacteria that use E2 as its sole source of carbon and energy for growth and identified them as Rhodococcus, and we named them DSSKP-R-001. For a better understanding of the metabolic potential of the strain, whole genome sequencing of Rhodococcus DSSKP-R-001 and annotation of the functional genes were performed. The genomic sketches included a predicted protein-coding gene of approximately 5.4 Mbp with G + C content of 68.72% and 5180. The genome of Rhodococcus strain DSSKP-R-001 consists of three replicons: one chromosome and two plasmids of 5.2, 0.09, and 0.09, respectively. The results showed that there were ten steroid-degrading enzymes distributed in the whole genome of the strain. The existence and expression of estradiol-degrading enzymes were verified by PCR and RTPCR. Finally, comparative genomics was used to compare multiple strains of Rhodococcus. It was found that Rhodococcus DSSKP-R-001 had the highest similarity to Rhodococcus sp. P14 and there were 2070 core genes shared with Rhodococcus sp. P14, Rhodococcus jostii RHA1, Rhodococcus opacus B4, and Rhodococcus equi 103S, showing evolutionary homology. In summary, this study provides a comprehensive understanding of the role of Rhodococcus DSSKP-R-001 in estradiol-efficient degradation of these assays for Rhodococcus. DSSKP-R-001 in bioremediation and evolution within Rhodococcus has important meaning.